The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/mnfr.200400020
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to nephrotoxic Ochratoxin A enhances collagen secretion in human renal proximal tubular cells

Abstract: Ochratoxin A (OTA) is a nephrotoxic mycotoxin. There is evidence that OTA leads to cortical interstitial nephropathies in humans, associated with fibrosis. No data are available on the effect of OTA-induced collagen secretion from renal cortical cells. As kidney cortex mainly consists of proximal tubules, we investigated the effect of OTA on particular collagens (I, III, IV) in a well-established proximal tubular cell line (opossum kidney (OK) cells) and in primary cultured human renal proximal tubular epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…We could show previously that OTA induces fibrosis in proximal tubular cells (Sauvant et al, 2004(Sauvant et al, , 2005. Thus, we investigated the effect of ERK1/2 inhibition on OTA-induced secretion of collagen I, III, and IV by specific ELISA technique (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We could show previously that OTA induces fibrosis in proximal tubular cells (Sauvant et al, 2004(Sauvant et al, , 2005. Thus, we investigated the effect of ERK1/2 inhibition on OTA-induced secretion of collagen I, III, and IV by specific ELISA technique (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we recently investigated the effect of OTA on selected parameters of chronic renal cortical disease in proximal tubular cell lines (Sauvant et al, 2004(Sauvant et al, , 2005. In the mentioned studies, we could show that OTA induces loss of cell number, necrosis and apoptosis, fibrosis, inflammation, and epithelial to mesenchymal transition in proximal tubular cells.…”
mentioning
confidence: 99%
“…Transdifferentiation has furthermore been discussed in relation to BEN (Markovic-Lipkovski, 2002). Indeed, Sauvant and colleagues hypothesized epithelialto-mesenchymal transition because of OTA-induced enhancement of collagen secrection in OK cells and primary human proximal tubular epithelial cells (RPTECs) (Sauvant et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The latter findings, coupled with the observations that fibroblasts are less susceptible to ochratoxin-mediated toxicity (Grotegut et al, 2001;O'Brien et al, 2001), gave rise to the hypothesis that repeated exposure to ochratoxins alters normal renal epithelial cells, possibly converting them to a more fibroblast-like nature, thus, providing the rudiments for renal fibrosis (van Kooten et al, 2001). Support for this hypothesis was presented by the recent publication of Sauvant et al (2005), who described an increase in collagen synthesis in OK cells and primary human renal proximal tubular epithelial cells (RPTEC) following exposure to OTA. All of these observations are mostly descriptive in nature and need to be further characterized.…”
Section: Introductionmentioning
confidence: 90%
“…OTA has been classified as a possible human carcinogen (Group 2B) by the International Agency for Research on Cancer (IARC, 1993). OTA has been shown to be a nephrotoxic (Sauvant et al, 2005), hepatotoxic (Ayed-Boussema et al, 2012), teratogenic (Wangikar et al, 2005) and immunotoxic (Mechoud et al, 2012) mycotoxin to several species of animals, and it has been reported to cause kidney and liver tumors in mice and rats (Huff, 1991). OTA can be metabolized in the kidney, liver and intestines (Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%